Intention to use mobile text message reminders for medication adherence among hypertensive patients in North West Ethiopia: a cross-sectional study - Ehite Melaku Zewdu; Adina Demessie; Araya Mesfin Nigatu; Nebebe Demis Baykemagn (BMC, 2024)
Abstract Background Reminders via digital technology offer a novel and efficient means to address medication forgetfulness, as they are easily accessible and user-friendly for patients. In particular mobile text message reminders are more suitable for chronic patients, as they require few technical skills, can operate without internet connectivity, and are less expensive than other technologies. This study aimed to assess the intention to use mobile text message reminders for medication adherence among hypertensive patients at the Gondar City health facilities. Methods A facility-based cross-sectional study was conducted. A simple random sampling method was used to select 423 hypertensive patients. Data was collected from April 1 to May 15, 2023. Data was collected using Kobo Toolbox, and the collected data was exported to MS Excel. Subsequently, the data was imported and analyzed using the SPSS version 20. Binary and multivariable logistic regression analysis was employed to assess factors associated with the outcome variable. Result The finding indicates that 64.5% of the patients have an Intention to use mobile text message reminders for medication adherence. Perceived usefulness (AOR = 2.53: 95%CI: 1.41, 4.52), perceived ease of use (AOR = 3.28: 95% CI: 1.81, 5.95), forgetting to take medication (AOR = 2.20: 95%CI: 1.38, 3.50) and patient holds their mobile phone always (AOR = 1.96: 95%CI: 1.04, 3.68) were associated factors with outcome variable. Conclusion Forget taking medication, the patient holds their mobile phone always, Perceived ease of use and Perceived usefulness were significantly associated with the outcome variable. We recommend designing and implementing user-friendly text message reminder systems and educating hypertensive patients about the system's benefits.